Nasal reconstruction with auricular microvascular transplant - Pribaz, JJ (1993)
A free flap derived from the ascending helix of the ear has been used to reconstruct an anatomically diverse set of defects of the distal nose in 6 patients. Our cadaver injection studies have demonstrated that the blood supply to the auricular flap is via small, consistent branches from the superficial temporal artery. The patients were carefully selected, and most had failed prior attempts at reconstruction. The auricular flaps were used to reconstruct the nasal tip, ala, columella, and sill. The donor vessels were anastomosed either to the facial artery and vein or to vessels in the neck, via vein grafts. The flaps survived in all cases, but all patients required minor subsequent revision. The auricular donor site was closed by rotation and advancement of local tissue. This flap is presented as a surgical option for selected patients with complex defects of the distal nose, where excellent match of color and contour, predictable outcome, and avoidance of central facial donor site are desired.